Competent building elevation for incorporating base isolation in aseismic structure - Islam, A.B.M.; Jameel, Mohammed; Uddin, Md Alhaz; Jumaat, Mohd Zamin (2012)
The predominant lateral loads acting upon building structures are earthquake and wind induced forces. If wind load is much greater than earthquake load, the lateral force resisting system required to tackle wind loading may be enough to resist the smaller earthquake load. In this situation, a seismic base isolator will not bring any benefit to the building system. Furthermore, if time period of a building without isolator is greater, incorporation of isolator will not bring much difference to the building behavior with respect to seismic load. Additionally, for buildings with lower structural time periods, incorporation of an isolator will greatly alter the seismic behavior. In light of all of these facts, this study examines the buildings in Dhaka, intended for different heights and plan area, to establish critical height up to which earthquake is the dominant lateral load. It also examines the relationship that exists between building height and time period. The study shows that though seismic base shear governs up to larger building height, in case of greater heights, time periods are much larger than the most suitable value of limiting time period for incorporating an isolator. Realistic structural time period and governing seismic load envisage that a seismic base isolator can be efficiently incorporated for up to 30 similar to 40m structural height at low to medium soil conditions for aseismic RCC building structures. (c) 2012 Elsevier B.V...Selection and peer-review under responsibility of Bin Nusantara University